A Randomized Pilot Study of a Phone-Based Mindfulness and Weight Loss Program. Issue 4 (2nd October 2019) - Carpenter, Kelly M.; Vickerman, Katrina A.; Salmon, Erica E.; Javitz, Harold S.; Epel, Elissa S.; Lovejoy, Jennifer C.
ABSTRACT: This study evaluated the feasibility and efficacy of integrating mindfulness training into a phone-based weight loss program to improve outcomes in those with high levels of emotional eating. Participants were 75 enrollees into an employer-sponsored weight loss program who reported high levels of overeating in response to thoughts and feelings. Seventy-five overweight and obese participants (92% female, 65% Caucasian, aged 26 to 68 years) were randomized to the new mindfulness weight loss program (n = 50) or the standard behavioral weight loss program (n = 25). Both programs consisted of 11 coaching calls with health coaches and registered dietitians with supplemental online materials. Satisfaction, engagement, and percent weight lost did not significantly differ for intervention vs. control at six months. Intervention participants had significantly better scores at six-month follow-up on mindful eating, binge eating, experiential avoidance, and one mindfulness subscale. Exploratory analyses showed that improvements on several measures predicted more weight loss in the intervention group. This pilot study found that integrating mindfulness into a brief phone-based behavioral weight loss program was feasible and acceptable to participants, but did not produce greater weight loss on average, despite hypothesized changes in mindful eating. Only one third of intervention participants reported participating in mindfulness exercises regularly. Mechanisms of change observed within the intervention group suggest that for adults with high levels of emotional eating those who embrace mindful eating and meditation may lose more weight with a mindfulness intervention.